Comparative Efficacy of Intracanal Medicaments in Healing Apical Periodontitis: Insights from a Comprehensive Clinical Study - G. Priya Johnson; Shruti Kataria; Sravana Laxmi Penumaka; Bilal Ameer; Abdul Sattar Mohammed; Sabari Murugesan (Journal of Pharmacy and Bioallied Sciences)
Background: Apical periodontitis is a prevalent condition that necessitates effective intracanal medicaments for successful endodontic therapy. Materials and Methods: A randomized controlled clinical trial was conducted on 120 patients diagnosed with apical periodontitis. The patients were randomly assigned to three groups, Group A (calcium hydroxide), Group B (triple antibiotic paste), and Group C (chlorhexidine gel), with 40 patients in each group. Each medicament was placed in the root canal after standard endodontic procedures, and the patients were evaluated at 1, 3, and 6 months using radiographic assessment and clinical examination. The primary outcome measure was the reduction in lesion size, and secondary outcomes included pain relief and healing time. Results: After 6 months, Group B (triple antibiotic paste) showed the highest reduction in lesion size, with an average decrease of 75%, followed by Group C (chlorhexidine gel), with a 60% reduction, and Group A (calcium hydroxide), with a 50% reduction. Pain relief was observed in 85% of patients in Group B, 75% in Group C, and 65% in Group A. The average healing time was the shortest in Group B (4 months), compared to Group C (5 months) and Group A (6 months). Conclusion: Triple antibiotic paste demonstrated superior efficacy in healing apical periodontitis compared to calcium hydroxide and chlorhexidine gel.